THE DEVELOPMENT OF LEARNING ACTIVITIES BASED ON COMPETENCY-BASED LEARNING TO PROMOTE POLITICAL LITERACY OF UPPER SECONDARY SCHOOL STUDENTS - Buangam, Chitnarong; Srikolchan, Anchalee (Journal of Educational Review Faculty of Education in MCU, 2025)
This research study aimed to develop and evaluate the effectiveness of learning activities based on a competency-based learning approach in promoting the political literacy of upper secondary school students. The research procedure was divided into two phases: Phase 1 involved developing learning activities based on competency-based learning to promote political literacy among upper secondary school students, and Phase 2 focused on evaluating the outcomes of implementing these learning activities. The research sample consisted of 30 Mathayom 5 students enrolled in the Politics 101 course during the second semester of the 2024 academic year, selected using purposive sampling. The research instruments included the developed learning activities and a political literacy measurement for upper secondary school students. The data were analyzed using mean, standard deviation, and a dependent-samples t-test. The results of the study were as follows: 1) The developed learning activities consisted of the principles of competency-based learning and the steps for implementing this approach: Step 1, determining competency-based learning objectives; Step 2, integrating learning content; Step 3, designing competency-based learning activities; and Step 4, reflection and evaluation. Additionally, guidelines for competency-based assessment and evaluation were established. 2) Students who participated in these learning activities demonstrated significantly higher levels of political literacy after the intervention compared to before, at the statistical significance level of p< .05.